Optimization and test of pneumatic lifting seed distributor for maize plot seeder - Song, Qingbin; Zhao, Pengfei; Bi, Yubin; Fu, Zuoli; Huang, Yuxiang; Zheng, Yi (Frontiers in Plant Science, 2025)
IntroductionThe seed distributors are the core components of the plot seeder. Their functions are to distribute the seeds evenly to the seed metering device corresponding to each sowing row. In order to solve the problem of uneven seed distributing of the seed distributor of maize plot seeder under tilted state, this study designed a pneumatic lifting seed distributor and optimized its structure and working parameters.MethodsA theoretical analysis of the seed distributing process was carried out. The sliding, rolling and bouncing states of maize seeds on the cone were analyzed. The parameters’ range that affected the seed distributing uniformity of the seed distributor were determined through single-factor tests. A three-factor three-level Box-Behnken design (BBD) test was carried out with cone height, seed storage tube diameter and seed storage tube lifting height as the test factors.ResultsIt was concluded that sliding down along the cone surface was the best movement way of seed distributing. The BBD test results showed that cone height, seed storage tube diameter and seed storage tube lifting height had highly significant effects on the variation coefficients of seed distributing uniformity in the three situations that the seed distributor were horizontally tilted at 0° vertically tilted at 0°, horizontally tilted at 5° vertically tilted at 0°, and horizontally tilted at 5° vertically tilted at 5°. The optimal structural and operational parameter combination of the seed distributor were as follows: cone height of 77 mm, seed storage tube diameter of 70 mm, and seed storage tube lifting height of 42 mm. Under this parameter combination, the bench test was carried out to verify that the variation coefficient of seed distributing uniformity were 5.13%, 7.07%, and 6.54% when the seed distributor were in three tilted states. The test results were basically consistent with the predicted values. The variation coefficient of seed distributing uniformity in field test was 1.23 percentage points lower than that of the traditional seed distributor.DiscussionThe pneumatic lifting seed distributor has better seed distributing effect than traditional seed distributor.The research provided a technical reference for the optimization and improvement of the seed distributor of the plot seeder.